2013
DOI: 10.1007/s11207-013-0273-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in the Rigidity Spectrum of Forbush Decreases Based on Neutron Monitor Data

Abstract: The Forbush decrease (Fd) of the Galactic cosmic ray (GCR) intensity and disturbances in the Earth's magnetic field generally take place simultaneously and are caused by the same phenomenon, namely a coronal mass ejection (CME) or a shock wave created after violent processes in the solar atmosphere. The magnetic cut-off rigidity of the Earth's magnetic field changes because of the disturbances, leading to additional changes in the GCR intensity observed by neutron monitors and muon telescopes. Therefore, one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…In the context of interstellar shocks, such as supernova remnant shocks, usually simple diffusion models are employed but it was shown recently that the form of the diffusion coefficient can have a strong impact on the cosmic ray spectrum [see Ferrand et al , ]. Analytical forms of the diffusion coefficients are also required for studies of solar modulation and space weather [see, e.g., Alania et al , ; Engelbrecht and Burger , ; Manuel et al , ; Potgieter et al , ; Zhao et al , ; Engelbrecht and Burger , ]. To understand the propagation of cosmic rays in different astrophysical environments, the knowledge of transport parameters is also required [see, e.g., Shalchi and Büsching , ; Thornbury and Drury , ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of interstellar shocks, such as supernova remnant shocks, usually simple diffusion models are employed but it was shown recently that the form of the diffusion coefficient can have a strong impact on the cosmic ray spectrum [see Ferrand et al , ]. Analytical forms of the diffusion coefficients are also required for studies of solar modulation and space weather [see, e.g., Alania et al , ; Engelbrecht and Burger , ; Manuel et al , ; Potgieter et al , ; Zhao et al , ; Engelbrecht and Burger , ]. To understand the propagation of cosmic rays in different astrophysical environments, the knowledge of transport parameters is also required [see, e.g., Shalchi and Büsching , ; Thornbury and Drury , ].…”
Section: Introductionmentioning
confidence: 99%
“…• For solar modulation studies (see, e.g., Alania et al 2013, Engelbrecht & Burger 2013, Manuel et al 2014);…”
Section: Discussionmentioning
confidence: 99%
“…A dependence of the Fd amplitude on the rigidity of GCR particles is one of its essential characteristics, called the rigidity spectrum of the Fd. The rigidity dependence of the GCR intensity in different phases of the Fd was presented in [4,5,6,7,8,9,10] and references therein. In these papers it has been shown that a rigidity spectrum δ D(R)/D(R) ∝ R −γ of the vast majority of the Fds gradually hardens during the decreasing and minimum phases of the Fd and gradually softens in the recovery phase of the Fd.…”
Section: Introductionmentioning
confidence: 99%
“…In these papers it has been shown that a rigidity spectrum δ D(R)/D(R) ∝ R −γ of the vast majority of the Fds gradually hardens during the decreasing and minimum phases of the Fd and gradually softens in the recovery phase of the Fd. Moreover, the time profiles of the Fds rigidity spectrum are associated with the changes of the power spectral density (PSD) of the interplanetary magnetic field (IMF) turbulence (PSD = P( f f 0 ) −ν , where P is power, f is frequency and f 0 is normalization frequency) [4,5,6,7,8,9,10]. Precisely, changes in the exponent γ of the power law rigidity R spectrum are explicitly determined by the changes of the exponent ν of the PSD in the range of frequency f ∈ [10 −6 , 10 −5 ] Hz of the IMF turbulence, to which neutron monitors and ground muon telescopes respond.…”
Section: Introductionmentioning
confidence: 99%